TWO NOVEL INSERTION/DELETION VARIANTS OF THE CRTC3 GENE AND THEIR EFFECTS ON GROWTH TRAITS IN FOUR DIFFERENT CHINESE SHEEP BREEDS - S. He; H. Zhao; S. Wang; Y. Zhu; X. Yu; X. Sun (Journal of Animal and Plant Sciences, 2019)
Cyclic adenosine monophosphate response element binding (CREB)-regulated transcription coactivator 3 (CRTC3) which is interfere with the metabolism of adipose tissue through distraction catecholamine signaling pathways. On account of its impact on the metabolism, CRTC3 gene may effect mammalian growth and development. In this study, 605 samples were used to detect the Insertion/Deletion (indel) of CRTC3 gene in sheep by agarose gel and DNA sequencing. In four varieties of Chinese domestic sheep breeds, 12 bp (NC_019475.2:g.21152662_ 21152663ins CAGGGGCACGTG) and 31bp (NC_019475.2:g.21114157_ 21114187delTTGATGGGTTGCAAAGAGTCAGACATG ACTT) indels polymorphisms of CRTC3 gene were first evaluated. The two indel loci were significantly associated with sheep growth-related traits including body length, chest depth, hip height, chest circumference and body weight. The allelic frequencies distribution of locus2 were significantly different between the high fecundity breeds (HS) and low fecundity breeds (TS, LFTS) on an χ2 test (P<0.05). This study demonstrated that the 12bp and 31bp indels could extend the spectrum of genetic variations of CRTC3 gene in sheep. Both the two loci may be considered as potential functional polymorphisms that may increase the growth traits in sheep.
Keywords: sheep; Cyclic adenosine monophosphate response element binding-regulated transcription coactivator 3 (CRTC3); Insertion/Deletion (indel); Growth traits